Delivery, Beam and Range Monitoring in Particle Therapy in a Highly Innovative Integrated Design - Bottura, L.; Felcini, E.; Ferrero, V.; Fiorina, E.; Monaco, V.; Pennazio, F.; de Rijk, G.; Cerello, P. (Frontiers in Physics, 2020)
The design of a particle therapy system that integrates an innovative beam delivery concept based on a static toroidal gantry and an imaging configuration suitable for beam and online range monitoring is proposed and discussed. Such approach would provide a compact and cost-effective layout, with a highly flexible and fast beam delivery, single particle counting capability for fast measurement of beam fluence and position and a precise real time verification of the compliance between the treatment delivery and its prescription. The gantry configuration is discussed, presenting an analysis of the residual magnetic field in the bore and of the feasibility of irradiating a realistic target volume. Moreover, the expected performance of the PET-based range monitor is assessed through Monte Carlo simulations, showing a precision in the reconstruction of the activity distribution from a clinical treatment plan better than the state-of-the-art devices. The feasibility of the proposed design is then discussed through an assessment of the technological improvements required to actually start the construction and commissioning of a system prototype.